2017
DOI: 10.3390/polym9120718
|View full text |Cite
|
Sign up to set email alerts
|

PVDF Membrane Morphology—Influence of Polymer Molecular Weight and Preparation Temperature

Abstract: Abstract:In this study, we successfully prepared nine non-woven, supported polyvinylidene fluoride (PVDF) membranes, using a phase inversion precipitation method, starting from a 15 wt % PVDF solution in N-methyl-2-pyrrolidone. Various membrane morphologies were obtained by using (1) PVDF polymers, with diverse molecular weights ranging from 300 to 700 kDa, and (2) different temperature coagulation baths (20, 40, and 60 ± 2 • C) used for the film precipitation. An environmental scanning electron microscope (ES… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…Following physical and morphological characterisation of the materials, the emphasis was shifted to test the reproducibility of the fibre membranes and their piezoelectric characteristics. FTIR revealed the characteristic peaks of β-phase (840 cm -1 ) and no prominent peaks for γ-phase (833 cm −1 and 1233 cm −1 ) for both types of fibres fabricated [65,66], as shown in Figure 4b. X-RD results further confirm the presence of β-phase in the fibre membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Following physical and morphological characterisation of the materials, the emphasis was shifted to test the reproducibility of the fibre membranes and their piezoelectric characteristics. FTIR revealed the characteristic peaks of β-phase (840 cm -1 ) and no prominent peaks for γ-phase (833 cm −1 and 1233 cm −1 ) for both types of fibres fabricated [65,66], as shown in Figure 4b. X-RD results further confirm the presence of β-phase in the fibre membranes.…”
Section: Resultsmentioning
confidence: 99%
“…This feature should be considered during the analysis of the relationship between molecular weight and content of the β-phase. For example, Haponska et al observed the increase of the β-phase content with the decrease of molecular weight by preparing PVDF membranes with a phase inversion precipitation method [ 76 ]. They found that low molecular weights increase the amount of polymer chain entanglement, which improved the β-phase.…”
Section: Piezoelectric Pvdf By Electrospinningmentioning
confidence: 99%
“…It has been shows that polymers with high molecular weights are more suitable for fiber spinning [71] and a higher molecular weight of precursor PVDF yield nanofibers with bigger diameters [72]. The molecular weight of precursor PVDF also affects the fraction of β-phase in the produced nanofibers [73]. When polymer has high molecular weight, the formation of bundles of fibrils is easy in the cross-linked polymer fiber [74,75].…”
Section: Molecular Weightmentioning
confidence: 99%